2020
DOI: 10.24875/acm.19000195
|View full text |Cite
|
Sign up to set email alerts
|

Factibilidad en la estimación ecocardiográfica de parámetros del ventrículo derecho en posición prono

Abstract: Introducción: Los parámetros cardiacos ecocardiográficos en posición de decúbito prono usualmente se obtienen con sonda esofágica. Se desconoce la factibilidad de obtenerlos mediante aproximación transtorácica. Objetivo: Estimar la factibilidad para obtener parámetros del ventrículo derecho mediante ecocardiografía transtorácica en el sujeto en posición de decúbito prono. Métodos: Diseño piloto de serie de casos consecutivos sin enfermedad cardiopulmonar. Se acotaron variables demográficas, signos vitales y ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
1
0
1
Order By: Relevance
“…Santos-Martínez и соавт. на примере 50 здоровых добровольцев продемонстрировали сопоставимость результатов оценки правых отделов сердца у пациентов в положении лежа и в Pr-позиции [22]. Аналогичные результаты были получены у пациентов с ковид-обусловленным ОРДС [17,20].…”
Section: Discussionunclassified
“…Santos-Martínez и соавт. на примере 50 здоровых добровольцев продемонстрировали сопоставимость результатов оценки правых отделов сердца у пациентов в положении лежа и в Pr-позиции [22]. Аналогичные результаты были получены у пациентов с ковид-обусловленным ОРДС [17,20].…”
Section: Discussionunclassified
“…In patients not on invasive mechanical ventilation, the feasibility of evaluating the left ventricle (LV) through its ejection fraction and longitudinal global strain was archived 4 . Another analysis, also in patients not undergoing invasive mechanical ventilation, but aimed at analyzing the right ventricle (RV) in 50 patients, showed that systolic function parameters such as tricuspid annulus plane systolic excursion (TAPSE) could be obtained in 100% of their cases 5 . On the other hand, the evaluation of the IVC and the state of volemia has been evaluated in patients who required invasive mechanical ventilation and prone position during surgery, but from the right side of the patient 2 .…”
mentioning
confidence: 99%